Spatial tuning of acoustofluidic pressure nodes by altering net sonic velocity enables high-throughput, efficient cell sorting. Issue 4 (21st February 2015) - Jung, Seung-Yong; Notton, Timothy; Fong, Erika; Shusteff, Maxim; Weinberger, Leor S.
<x xml:space="preserve">Abstract</x> We report a two-channel fluidic device that allows geometry-independent tuning of acoustic nodes for high-throughput particle sorting.